Cavity-assisted modulation instability lasing of a fiber ring laser - Shao, G. D. (2020)
We report on the experimental evidences of cavity-assisted modulation instability (CAMI) lasing of fiber lasers. We first reviewed the theory of CAMI. We then presented experimental evidences of CAMI lasing of fiber lasers with either an anomalous or a normal dispersion cavity. It is shown that even in a fiber laser without any mode-locking element in cavity, if the orientation of the intracavity polarization controller is changed, a CW emission could be suddenly converted into a stable periodic pulse train emission. Moreover, the repetition rate of the pulse train can be adjusted over a wide range from the fundamental cavity repetition frequency to hundreds of GHz by changing the cavity detuning. We point out that the CAMI lasing should be a general effect of lasers with a nonlinear cavity.